Geographical and Seasonal Patterns of Geosmin and 2-Methylisoborneol in Environmental Water in Jiangsu Province of China - Zhen Ding; Shifu Peng; Yuqin Jin; Zhoubin Xuan; Xiaodong Chen; Lihong Yin (Journal of Analytical Methods in Chemistry)
This study was conducted to obtain the basic data of two common odorants—geosmin and 2-methylisoborneol (GSM and 2-MIB)—in environmental water. More specifically, the headspace solid-phase microextraction coupled to gas chromatography mass spectrometry (HS-SPME/GC-MS) was applied to determine the levels of GSM and 2-MIB in water samples, and the samples were collected depending on water sources, conventional treatment processes, and seasons. The significant difference was shown for the 2-MIB levels of source water P<0.05, the concentrations of GSM and 2-MIB decreased significantly as treatment process of tap water moved forward (P<0.0001), and the significant differences for the levels of GSM and 2-MIB were observed among three sampling periods (P<0.01). The levels of GSM and 2-MIB in all water samples were lower than 10 ng L−1, the odor threshold concentration (OTC), and the conventional treatment process plays a significant role in removing odorants in tap water.